Factores clave en el desarrollo de la capacidad emprendedora de estudiantes universitarios - Mauricio Castillo-Vergara; Alejandro Álvarez-Marín; Mauricio Alfaro-Castillo; Jorge Sánchez Henríquez; Ignacio Pizarro Quezada (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
– This study aims to explore the key factors that may affect the entrepreneurial capacity of students of Higher Education Centers (CES). Once the factors were established, these were grouped into internal and external to the ESCs, then the AHP method was applied to determine the relative weights of each of the criteria to groups of experts belonging to different disciplines and Latin American countries. Through the consensus of the experts, the results indicate that internal factors that most influence the entrepreneurship of their students are "Entrepreneurial Spirit", "Work Experience" and "Performance of specific courses" and as external factors affect to a greater extent "The Networks", "Friends" and "Scope of development". The results of the study can be used as an important reference for educational establishments, to define strategies based on these factors, which help to improve ecosystems within their centers, effectively enhancing the entrepreneurial capacity of their students.
Keywords: I23; M13; M14; 330; entrepreneurship; Higher Education centers; entrepreneurial capacity; entrepreneurial ecosystem